2020
DOI: 10.1556/204.2020.00015
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal policy and growth in a small emerging economy: The case of Bulgaria

Abstract: The purpose of this article is to study the impact of fiscal policy on economic growth in Bulgaria for the period 1995–2018. The descriptive analysis is focused on the general trends in fiscal policy and tax structure. The influence of government spending and taxation on economic growth is studied through regressions on time-series data. The empirical estimates prove that taxation is a more reliable instrument of fiscal policy than government spending in terms of a small open emerging-market economy. The dilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…Thirdly, personal income appeared to be growth-friendly, this view is endorsed by Moyo et al (2021) and Maganya (2020) for South Africa and Tanzania respectively. While some studies discovered that personal income tax is harmful to economic growth as confirmed by Stoilova and Patonov (2020)…”
Section: Balasoiu Et Al (mentioning
confidence: 98%
See 2 more Smart Citations
“…Thirdly, personal income appeared to be growth-friendly, this view is endorsed by Moyo et al (2021) and Maganya (2020) for South Africa and Tanzania respectively. While some studies discovered that personal income tax is harmful to economic growth as confirmed by Stoilova and Patonov (2020)…”
Section: Balasoiu Et Al (mentioning
confidence: 98%
“…This chain effect will results into high economic growth, reduction of tax avoidance, stimulating competitiveness a well as reduction of tax evasion. Stoilova and Patonov (2020) conducted a study attempting to investigate the impact of fiscal policy on Bulgarian economy. The study paid particular attention to the effect of personal and corporate taxes and value added tax during1995-2018.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The second strand of literature covers the relationship between the fiscal sector and economic growth. These studies mostly dwell on the nexus between fiscal policy and economic growth, as fiscal policy instruments are the key variables in the fiscal sector (see [15][16][17][18] Nwite et al, 2019).…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Restrictive policies improve the situation in the public finance sector from the long-term perspective, contributing to moderate economic growth. Stoilova & Patonov (2020) prove that taxation is a more reliable instrument than government spending in a small open emerging-market economy. Benos (2009), examining the impact of fiscal policy on economic growth in European countries, notes the importance of the structure of public spending.…”
Section: Introductionmentioning
confidence: 97%